2014
DOI: 10.1111/appy.12141
|View full text |Cite
|
Sign up to set email alerts
|

Child abuse, disruptive behavior disorders, depression, and salivary cortisol levels among institutionalized and community‐residing boys in Mongolia

Abstract: Salivary cortisol data from a non-Western naturalistic setting support an association of reduced basal HPA activity with disruptive behavior disorders and caregiver attitudes toward discipline. These findings suggest HPA functioning may be a reflection of or mediate disruptive behavior disorders in children across ethnic and cultural settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 102 publications
(128 reference statements)
2
13
0
Order By: Relevance
“…Analytically, these measures represent interrelated but distinct aspects of the psychobiology of stress and the stress response: i.e., the HPA axis and the sympathetic nervous system (64)(65)(66)88). Salivary analytes such as these are increasingly used to assess psychosomatic stress in non-WEIRD contexts, thus providing both methods and interpretive frameworks for our own research (9,16,69,(89)(90)(91)(92)(93)(94)(95). Alongside the two physiological analytes, we also elicited responses from Sahariya to the Bradford Somatic Index (BSI) (96), a psychiatric scale validated to capture mental health disorders among South Asian populations.…”
Section: Research Hypotheses and Analytical Planmentioning
confidence: 99%
“…Analytically, these measures represent interrelated but distinct aspects of the psychobiology of stress and the stress response: i.e., the HPA axis and the sympathetic nervous system (64)(65)(66)88). Salivary analytes such as these are increasingly used to assess psychosomatic stress in non-WEIRD contexts, thus providing both methods and interpretive frameworks for our own research (9,16,69,(89)(90)(91)(92)(93)(94)(95). Alongside the two physiological analytes, we also elicited responses from Sahariya to the Bradford Somatic Index (BSI) (96), a psychiatric scale validated to capture mental health disorders among South Asian populations.…”
Section: Research Hypotheses and Analytical Planmentioning
confidence: 99%
“…In addition, this systematically and locally developed tool may aid efforts in global mental health and neuroscience (Stein et al, 2015) to identify cross-cultural biological markers and mechanisms related to DBDs. Prior studies with boys in Nepal and other regions of Asia have demonstrated associations of disruptive behaviors with hypocortisolism in naturalistic assessments (Hruschka, Kohrt, & Worthman, 2005; Brandon A Kohrt et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Among school‐aged children, both early and current psychosocial stress have been found to be associated with hypersecretion (Cicchetti & Rogosch, ; Gustafsson, Gustafsson & Nelson, ), and, similar to adults, hyposecretion is associated with PTSD (Feldman, Vengrober, Eidelman‐Rothman & Zagoory‐Sharon, ). In addition, children with attention deficit hyperactivity disorder (Isaksson, Nilsson, Nyberg, Hogmark, & Lindblad, ) or disruptive behaviour disorder (Kohrt, Hruschka, Kohrt, et al ) have been found to show low cortisol levels.…”
Section: Cortisol Dysregulationmentioning
confidence: 99%
“…Both maternal prenatal and postnatal mental health problems thus predicted children's later stress regulation, but in unique ways. We discuss the specific roles of direct biochemical Lindblad, 2012) or disruptive behaviour disorder (Kohrt, Hruschka, Kohrt, et al 2015) have been found to show low cortisol levels.…”
mentioning
confidence: 98%